Lao People's Democratic Republic : Technical Assistance Report-Risk-Based Banking Supervision. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2019)
This Technical Assistance report on the Lao People's Democratic Republic provides advice toward implementing risk-based supervision (RBS). Special attention needs to be given to expediting the formal approval of the RBS manual and fully implementing RBS methods in practice. Although this could be delayed due to other supervisory priorities, it is considered essential as the quality of supervision is improved by the practical application of RBS tools and learning-by-doing. The root causes of risks should be better identified, and greater attention should be paid to well-reasoned analysis of risks and the accompanied supervisory action. In addition, the mission advised additional modification of these documents to enhance its usefulness and quality. With respect to foreign-branch supervision, special consideration should be given to the extent of adequate oversight by the branch head office, supervision by the home supervisor, and overall financial condition of the foreign banking group. The mission provided examples of qualitative criteria for foreign-branch rating.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet